Experimental and computational studies on the Cinchona anchored calixarene catalysed asymmetric Michael addition reaction. Issue 52 (6th June 2022) - Sharma, Pragati R; Malik, Apoorva; Bandaru, Sateesh; Vashisth, Kanika; Rana, Nirmal K; Sharma, Rakesh K
Abstract : We report lower-rim Cinchona anchored calix[4]arene cationic catalysts for the enantioselective Michael addition reaction. Abstract : Lower-rim Cinchona anchored calix[4]arene cationic catalysts were developed for asymmetric Michael addition of acetylacetone to β-nitrostyrenes. The desired Michael adducts were formed with high yields and enantioselectivities. Density functional theory investigations throw light on the catalyst–substrate interaction and the reaction mechanism.